(untitled) (Ameghiniana, 2014)
The structure of silicified axes of palm was studied. The age of plantiferous beds, after Andreis el al. (1991) is Late Cretaceous. The fossil structures were compared with actual palm axes. On the basis of the characteristics of vascular bundles; interfasicular parenchyma; fibres and phleorn, the materials were assigned to three Subfamilies: Sabaloideae, Coccoideae, and Phoenicoideae. The endosperm structure of fossil fruits was also studied, showing great similarity with the fruits of actual Phoenix canriensis